Abdominal tumor syndrome in children (Perioperaciina Medicina, 2019)
This article deals with the actual problem of the syndrome of abdominal tumor in children. A complex of clinical symptoms and signs is described that characterize the presence of a tumor-like formation in the abdominal cavity of various origins. The various causes of the occurrence of volumetric processes in the abdominal cavity are examined. Considering that the volumetric process in the abdominal cavity in children is a common situation, and it occurs not only with true tumors, the article describes various clinical situations that lead to the syndrome of abdominal tumor in children.
Keywords: tumor; abdominal cavity; treatment; diagnostics; child